UTILIZATION OF POWERPOINT MEDIA TO IMPROVE STUDENT LEARNING OUTCOMES - Listini Ndari; Beldiana Teofani Ndore; Ainun Jariyah; Veronika P. S. M. Wae; Yosephina Payu Wao; Jumilah Gago (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2026)
This community service aims to improve students’ learning outcomes using technology-based learning media, particularly interactive Microsoft PowerPoint, in Biology learning for twelfth-grade students at SMA Adhyaksa Ende. The study was motivated by low student achievement caused by the dominance of teacher-centred lecture methods. The implementation method consisted of preparation and instructional stages. The preparation stage included lesson plan development, curriculum-based material design, and training in the use of technology for creating interactive PowerPoint media. The implementation stage involved presenting cell division material using slides containing text, images, videos, animations, and interactive quizzes. The results indicated an improvement in students’ understanding, as reflected in their ability to restate the material and their increased accuracy in answering evaluation questions. These findings are consistent with previous studies highlighting the effectiveness of interactive PowerPoint in enhancing student engagement and learning outcomes. Therefore, systematically and attractively designed PowerPoint media can serve as an innovative alternative to improve the quality of classroom instruction.